Vocational School Members’ Responses to English Summative Mobile-Based Assessment during the Study from Home Period - Muljani; Suwartono, Tono (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2022)
The research aims to reveal the responses to English summative Mobile-Based assessment during the Study from Home period of the vocational school members of State Vocational School 1 of Banyumas in Central Java, Indonesia. This kind of Mobile-Based assessment was administered due to the circular letter about the implementation of National Education during the emergency of Covid 19. Therefore the school adopted the policy to carry out the summative assessment by using students’ mobile device at home. The participants of this study were the stakeholder (Vice Principal of curriculum), an English teacher, and three students. The data was collected through semi-structured interviews. The data was transcribed (write down verbatim) and analyzed inductively. The data analyzed showed that the schools members responded to English summative Mobile-Based assessment positively, although there were some negative responses for certain cases. The findings are able to answer the research question which is dealing with the participants’ response. The participants gave various responses which are different from one another. Above all, in the conclusion the researcher could obtain the advantages and few disadvantages of the implementation of English summative Mobile-Based assessment.